Undercover protection - Black, Maggie K. (Love inspired suspense., 2021)
"When Leia Dukes is kidnapped at her family farm, the last person she expects to rescue her is the farmhand who broke her heart. With Leia's life on the line, Jay Brock reveals his secret: he's an undercover police officer hunting a serial killer - and there's evidence in her childhood home. Jay might be Leia's only hope of staying alive, but can she trust him again?" -- Back cover.